Effects of increasing dietary inclusion of camelina cake on growth performance of growing-finishing pigs1. Issue 3 (26th August 2021) - Hilbrands, A M; Johnston, L J; Cox, R B; Forcella, F; Gesch, R; Li, Y Z
Abstract: The objective of this experiment was to determine the dietary inclusion rate of camelina cake (CC) that would support the growth performance of growing-finishing pigs similar to that of a corn-soybean meal-based diet. Pigs ( n = 192; BW = 35.2 kg; Duroc x (Yorkshire x Landrace)), balanced for sex and initial weight, were assigned to pens (8 pigs/pen) and pens were assigned randomly to one of four dietary treatments (6 pens/treatment). Treatments consisted of a non GMO corn-soybean meal control diet (CON ), or CON containing 5% (5CC ), 10% (10CC ), or 15% (15CC ) camelina cake. Feed disappearance on a pen basis and individual body weights of pigs were recorded every other week to calculate average daily gain (ADG), average daily feed intake (ADFI), and gain to feed ratio (G:F) on a pen basis. Prior to harvest, real-time ultrasonic measurements of back fat depth and loin eye area were collected on all live pigs. Pigs were harvested as a single group at about 23 weeks of age at a commercial abattoir. Data were analyzed using Proc Glimmix with dietary treatment as a fixed effect and pen serving as the experimental unit. Growth performance data collected over time were analyzed using repeated measures within the Proc Glimmix procedure. Overall, pigs fed CON exhibited similar ADG to those consuming 5CC and higher ADG than pigs consuming 10CC and 15CC diets (1.10 kg vs. 1.05 kg for 10CC and 1.02 kg for 15CC; P < 0.05 for both mean comparisons). Pigs fed CON consumed more feed than pigs fed any of the CC diets (ADFI = 2.66 kg for CON vs. 2.46 kg for 5CC, 2.46 kg for 10CC and 2.47 kg for 15CC; P < 0.05 for all). These differences resulted in heavier ( P < 0.05) CON-fed pigs at marketing than 10CC or 15CC-fed pigs. There were no differences in any carcass traits analyzed. From these data, we conclude that feeding up to 5% CC in corn-soybean meal-based diets did not negatively influence growth performance, or carcass traits of growing-finishing pigs.